Erythrodermic psoriasis improved by tildrakzumab: a case report - Giampaolo Trevisan; Lerica Germi; Luigi Naldi (PAGEPress Publications, 2022)
Erythrodermic psoriasis (EP), clinically defined as prominent erythema and scaling affecting almost the entire skin surface, is a severe form and a rare variant of psoriasis. The treatment may require hospital admission with monitoring of vital signs and use of immunosuppressive drugs. Newer biological drugs, including anti-TNF, anti-IL-17, and anti-IL-12/23 agents, even if not specifically developed for the treatment of erythrodermic psoriasis, have been used successfully in single cases or in small case series. Tildrakizumab is an IgG1ҡ monoclonal antibody that selectively binds to the p19 subunit thereby inhibits the interaction of interleukin 23 (IL-23) with its receptor and thus inhibits the release of IL-23 mediated proinflammatory cytokines. We present a case of EP in an obese man (Body mass index 35.2) successfully and safely treated with Tildrakizumab.